2020
DOI: 10.1091/mbc.e20-01-0085
|View full text |Cite
|
Sign up to set email alerts
|

Measuring nucleus mechanics within a living multicellular organism: Physical decoupling and attenuated recovery rate are physiological protective mechanisms of the cell nucleus under high mechanical load

Abstract: Nuclei within cells are constantly subjected to compressive, tensile and shear forces, which regulate nucleoskeletal and cytoskeletal remodeling, activate signaling pathways and direct cell-fate decisions. Multiple rheological methods have been adapted for characterizing the response to applied forces of isolated nuclei and nuclei within intact cells. However, in vitro measurements fail to capture the viscoelastic modulation of nuclear stress-strain relationships by the physiological tethering to the surroundi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…This is likely the result of altered nuclear stiffness and lower elasticity, suggesting that aged nuclei are under constant self-induced stretch. A similar phenomena is observed when the LINC complex is impaired ( Zuela-Sopilniak et al, 2020 ). When nuclei are exposed to outside forces that deform the nuclear envelope morphology, NPC are redistributed and stretched, increasing transcription factor nuclear import ( Elosegui-Artola et al, 2017 ; Hoffman et al, 2020 ).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This is likely the result of altered nuclear stiffness and lower elasticity, suggesting that aged nuclei are under constant self-induced stretch. A similar phenomena is observed when the LINC complex is impaired ( Zuela-Sopilniak et al, 2020 ). When nuclei are exposed to outside forces that deform the nuclear envelope morphology, NPC are redistributed and stretched, increasing transcription factor nuclear import ( Elosegui-Artola et al, 2017 ; Hoffman et al, 2020 ).…”
Section: Discussionsupporting
confidence: 74%
“…Nuclear deformations are also found in aged nuclei ( Haithcock et al, 2005 ; Pérez-Jiménez et al, 2014 ), along with compromised nucleocytoplasmic transportation ( D'Angelo et al, 2009 ). Recently, it was shown that nuclei of aged C. elegans are more susceptible to damaging effects from outside stretch forces ( Zuela-Sopilniak et al, 2020 ). This is likely the result of altered nuclear stiffness and lower elasticity, suggesting that aged nuclei are under constant self-induced stretch.…”
Section: Discussionmentioning
confidence: 99%
“…[35] It is well known that on short time scales, nuclei can behave visco-elastically. [12,15,18,27,[36][37][38][39][40][41] These measurements are typically on the time scale of several seconds, while our observations are on the order of minutes to hours. Thus, it is difficult to extrapolate the shortterm measurements to the long-timescale behavior.…”
Section: Discussionmentioning
confidence: 99%
“… 249 Furthermore, many of the methods describe previously, such as AFM and MM, simply cannot access individual nuclei in vivo . More broad-scale deformation techniques such as substrate stretching have been able to circumvent this, 250 but there still exists a dearth of techniques capable of measuring nuclear mechanical properties within tissue samples. This motivates a new frontier of tool development research aimed at combining novel force probes with advanced microscopy to better enable studies of the physical role of the nucleus in tissue morphogenesis and embryogenesis.…”
Section: Perspective and Outlookmentioning
confidence: 99%